Future of CO2 Capture, Transport and Storage Projects Analysis using a Systemic Risk Management Approach - Samadi, Jaleh (SpringerBriefs in Environmental Science,, 2018)
This book presents a summary of a three-year research project on risk management for the Capture, Transport and Storage of CO2 (CTSC), offering an in-depth study on complex sociotechnical systems and systemic modeling. Approaching CTSC as a complex sociotechnical system, this book proposes systemic modeling as a decision-making aid. It offers a means of decision-making for the development of CTSC projects in the real-world context, where the future of the technology is uncertain. Risk management is considered as a means of control that can provide a control structure for the whole system. The risks associated with CTSC are not exclusively technical in nature; CTSC also faces a number of further uncertainties, from development to commercial scales. A major question concerning CTSC at the current scale of development is: "What are the factors explaining the success or failure of CTSC projects in different contexts?" In order to answer this question, the book proposes a systemic risk management framework based on the system dynamics and STAMP (Systems-Theoretic Accident Model and Processes) concepts. .